Dog Man : Big Jim begins - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (Pilkey, Dav, 1966- Dog Man, 2024)
"Join Dog Man and your favorite supa buddies as they save the city from a dastardly new wrongdoer!"--